Same-Sex Attracted, Not LGBQ: The Associations of Sexual Identity Labeling on Religiousness, Sexuality, and Health Among Mormons. Issue 7 (6th June 2020) - Lefevor, G. Tyler; Sorrell, Sydney A.; Kappers, Grace; Plunk, Ashley; Schow, Ron L.; Rosik, Christopher H.; Beckstead, A. Lee
ABSTRACT: In the Church of Jesus Christ of Latter-Day Saints (LDS church), beliefs about same-sex sexual attraction are carefully differentiated from beliefs about same-sex sexual behavior and identity, leading some to reject a lesbian, gay, bisexual, or queer (LGBQ) identity label in favor of declining a sexual identity or describing themselves as experiencing same-sex attraction (SSA). Using data from 1, 128 sexual minority Mormons recruited from both politically conservative and liberal circles, we examined the relationship between rejecting an LGBQ identity and religiousness, attitudes toward sexuality, and health outcomes. We found that Mormons who reject an LGBQ identity were significantly more religious and less content with their sexuality but had similar health outcomes relative to LGBQ Mormons. We posit that these differences are best understood by differences in group affiliation and support, intersectional experiences with minority stressors, and the lack of generalizability of LGBQ constructs to those who reject an LGBQ identity.